ANALISIS KETIDAKSESUAIAN KOMPETENSI PEGAWAI PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA MAGELANG - Nuri Nurhayati; Dwi Novitasari (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to analyze employee competency mismatches in the Financial and Asset Management Agency of the City of Magelang. The study was conducted from January to February 2019. This type of research is qualitative descriptive research. The technique of collecting data with interviews and documentation. Data analysis techniques by drawing conclusions from interviews. The results of the study show that not all employees have competencies that are in accordance with the work done, only 80% of employees are in line with the remaining 20% of employees are not suitable. Factors that cause employee competency mismatch are leadership authority or authority, education level, employee ability, seniority of rank and employee experience. Efforts to reduce employee competence mismatch, namely the placement of employees, need to pay attention to the level of education, seniority and years of service in order to achieve the right man on the right place. Magelang City Regional Financial and Asset Management Agency leaders are advised to pay attention to educational background, capabilities, employee specifications before deciding to place or transfer employees to occupy certain positions.